2015
DOI: 10.1371/journal.pone.0132275
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Rehabilitation Outcomes for Long Term Neurological Conditions: A Cohort Analysis of the Australian Rehabilitation Outcomes Centre Dataset for Adults of Working Age

Abstract: ObjectiveTo describe and compare outcomes from in-patient rehabilitation (IPR) in working-aged adults across different groups of long-term neurological conditions, as defined by the UK National Service Framework.DesignAnalysis of a large Australian prospectively collected dataset for completed IPR episodes (n = 28,596) from 2003-2012.MethodsDe-identified data for adults (16–65 years) with specified neurological impairment codes were extracted, cleaned and divided into ‘Sudden-onset’ conditions: (Stroke (n = 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 31 publications
3
18
0
2
Order By: Relevance
“…However, the gains in skills were not consistent across all domains, and some family and social skill items still needed further attention. The results were consistent with a previous study in Australia [16], which described significant motor FIM score improvement in inpatient rehabilitation for adults of SCI. Of course, the fact that scores did not change for eating, grooming, walking, and using stairs is to be expected [16,30].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, the gains in skills were not consistent across all domains, and some family and social skill items still needed further attention. The results were consistent with a previous study in Australia [16], which described significant motor FIM score improvement in inpatient rehabilitation for adults of SCI. Of course, the fact that scores did not change for eating, grooming, walking, and using stairs is to be expected [16,30].…”
Section: Discussionsupporting
confidence: 92%
“…The results were consistent with a previous study in Australia [16], which described significant motor FIM score improvement in inpatient rehabilitation for adults of SCI. Of course, the fact that scores did not change for eating, grooming, walking, and using stairs is to be expected [16,30]. More research is needed to understand how to improve these scores further within the SIBR and CBR settings.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The improvements made by heart and/or lung transplant recipients in the present study compare favorably with published rehabilitation outcomes of other patient populations. An average FIM gain of 22 points is considered a clinically important change, and is comparable in magnitude to improvements reported by national rehabilitation databases for large patient cohorts with debility and neurologic conditions . Similarly, mobility improvements in the present study well exceeded minimal clinically important differences reported for cardiopulmonary populations: 6MWT gains greater than 50 m are typically considered significant in most disease states (here, improvements averaged 79.6 m); and Berg Balance Scale improvements of greater than 7 points are considered clinically meaningfull (here, improvements averaged 18.2 points).…”
Section: Discussionsupporting
confidence: 83%
“…One questionnaire measured goal engagement and goal satisfaction, which accounted for a number of factors: how well goals matched patient priorities for rehabilitation; the extent to which patients agreed with the goals; the extent of choices available regarding goals; and the extent to which patients felt involved with/in charge of the goal-setting process. This questionnaire consisted of one item with a Likert-type scale ranging from excellent to none (Turner-Strokes et al, 2015).…”
Section: Methodsmentioning
confidence: 99%